2013
DOI: 10.1073/pnas.1220764110
|View full text |Cite
|
Sign up to set email alerts
|

Cotransplantation with specific populations of spina bifida bone marrow stem/progenitor cells enhances urinary bladder regeneration

Abstract: Spina bifida (SB) patients afflicted with myelomeningocele typically possess a neurogenic urinary bladder and exhibit varying degrees of bladder dysfunction. Although surgical intervention in the form of enterocystoplasty is the current standard of care in which to remedy the neurogenic bladder, it is still a stop-gap measure and is associated with many complications due to the use of bowel as a source of replacement tissue. Contemporary bladder tissue engineering strategies lack the ability to reform bladder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(108 citation statements)
references
References 36 publications
4
98
0
Order By: Relevance
“…However, in our previous study, we only detected cells positive for both CM-DiI and α-SMA, indicating that ASCs differentiated into smooth muscle cells but not CD31 + endothelial cells [15]. Sharma et al concluded that human mesenchymal stem cells or CD34 + haematopoietic stem/ progenitor cells become incorporated into the vessel wall at the onset of neovascularization, or as pericytes in nude mice [29]. While conventional stem cell therapies focus mainly on the ability of cells to differentiate and replace damaged or injured tissue, increasing evidence suggests that stem cells also exert functional activity by secreting bioactive factors that stimulate local and systemic responses [30,31].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…However, in our previous study, we only detected cells positive for both CM-DiI and α-SMA, indicating that ASCs differentiated into smooth muscle cells but not CD31 + endothelial cells [15]. Sharma et al concluded that human mesenchymal stem cells or CD34 + haematopoietic stem/ progenitor cells become incorporated into the vessel wall at the onset of neovascularization, or as pericytes in nude mice [29]. While conventional stem cell therapies focus mainly on the ability of cells to differentiate and replace damaged or injured tissue, increasing evidence suggests that stem cells also exert functional activity by secreting bioactive factors that stimulate local and systemic responses [30,31].…”
Section: Discussionmentioning
confidence: 59%
“…After the rats were euthanized by CO 2 asphyxiation, the rat bladders were excised for standard histological processing [29]. After ligating the bladder outlet by two non-absorbable 5-0 polypropylene sutures, the bladder was harvested by cutting between the two sutures.…”
Section: Histological and Immunofluorescence Analysismentioning
confidence: 99%
“…POC [poly (1,8-octanediol-co-citrate)] was synthesized and cell seeded as previously described [15]. Athymic female rats underwent bladder augmentation as previously described in detail [15].…”
Section: Bladder Augmentation Modelmentioning
confidence: 99%
“…However, in situations where adverse pathology or reaction to a foreign body plays a pivotal role in wound healing outcomes, alternative strategies must be employed to temper over- [12,13,14]. POC [poly (1,8-octanediolco-citrate)] is an elastomeric scaffold that has demonstrated the ability to mimic mechanical properties of the bladder while providing an amenable surface for cell growth [15,16,17]. MSCs have been shown to modulate acute inflammatory responses and ameliorate injury in vivo, while CD34 + HSPCs robustly induce angiogenesis and provide support for peripheral nerve regeneration [15,18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation